Sex representation in neurodegenerative and psychiatric disorders' preclinical and clinical studies - Tropea, Daniela (My University, 2023)
Many studies show the importance of biological sex for the onset, progression, and response to treatment in brain disorders. In line with these reports, health agencies have requested that all trials, both at the clinical and preclinical level, use a similar number of male and female subjects to correctly interpret the results. Despite these guidelines, many studies still tend to be unbalanced in the use of male and female subjects. In this review we consider three neurodegenerative disorders: Alzheimer's disease, Parkinson's disease, Amyotrophic lateral sclerosis, and three psychiatric disorders: Depression, Attention Deficit Hyperactivity Disorder, and Schizophrenia. These disorders were chosen because of their prevalence and their recognized sex-specific differences in onset, progression, and response to treatment. Alzheimer's disease and Depression demonstrate higher prevalence in females, whereas Parkinson's Disease, Amyotrophic lateral sclerosis, Attention Deficit Hyperactivity Disorder, and schizophrenia show higher prevalence in males. Results from preclinical and clinical studies examining each of these disorders revealed sex-specific differences in risk factors, diagnostic biomarkers, and treatment response and efficacy, suggesting a role for sex-specific therapies in neurodegenerative and neuropsychiatric disorders. However, the qualitative analysis of the percentage of males and females enrolled in clinical trials in the last two decades shows that for most of the disorders, there is still a sex bias in the patients' enrolment.
Keywords: Biological sex; Clinical trial; Neurodegenerative; Neuropsychiatric; Sex; Sex representation; Sex-specific difference; Neuroscience; neurobiology of brain disorders; sex equality; Autistic Spectrum disorders; Intellectual Disability; Mental Health/Psychosocial disability; Health